The complete mitochondrial genome sequence of the Metschnikowia bicuspidata (Metschnikoff, 1884), an emerging pathogen of 'milky disease' in Chinese mitten crab. Issue 7 (3rd July 2022) - Liu, Jiannan; Yu, Jieying; Pu, Senting; Shi, Xinran; Li, Yihao; Zhao, Xiaoran; Ye, Shigen
Abstract: The outbreak of milky disease of Chinese mitten crab caused by M. bicuspidata seriously restricted the development of the crab industry. In this study, the mitochondrial genome sequence of M. bicuspidata was assembled, annotated, and further analyzed. The results indicated that the complete mitochondrial genome of M. bicuspidata was 75, 095 bp, which contained two rRNAs, 23 tRNAs, and 13 protein-coding genes. The phylogenetic tree of 13 yeasts based on the complete mitochondrial genome was constructed which showed that M. bicuspidata (accession number OK514652) and M. bicuspidata (accession number MW147605.1) were clustered in a clade. To sum up, our research results would further provide essential data for the systematics and evolution study of M. bicuspidata .